Application of E-Module to Identify Students' Science Process Skills in the Practicum of Refraction on Prisms - Aprilita Ekasari; Maulidinah Maulidinah (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: The objective of this research is to determine the level of science process skills of Physics Education students at the University of Masumus in the practice of habituation in basic physics prisms towards the use of e-modules. Methodology: This research is a descriptive research type. The approach used in this research is a quantitative approach. The implementation of this research was conducted in October 2019. The number of samples in this study were all 2018 physics education students, totaling 40 people. This study used a sampling technique, namely total sampling. Main Findings: The results of research conducted by researchers, it is known. In the Science Process Skills Research of Physics Education Students at the University of Masumus in the prism refraction practicum using the e-module, the results were very good, this can be seen from the percentage results for each indicator. the use of e-modules can increase the level of student process skills in carrying out practicum activities. Novelty/Originality of Research: Novelty in research is in the form of analyzing the science process skills possessed by physics education students at the University Masumus.